Implementasi Otonomi Desa Berdasar Undang-Undang Nomor 6 Tahun 2014 Tentang Desa Di Kabupaten Minahasa - Mamengko, Rudolf Sam; Sondakh, Max Karel; Tampi, Butje (Lembaga Dakwah dan Pembangunan Masyarakat Universitas Cokroaminoto Yogyakarta (LDPM UCY), 2024)
The aim of the research is to identify the readiness of village officials regarding the implementation of Law Number 6 of 2014 concerning Villages (UUDs) in the field of development in Minahasa. The research also utilizes normative legal research with an emphasis on normative juridical research. The binding legal force of the Constitution has been recognized in the regulations regarding the Formation of Legislative Regulations in 2011. Furthermore, the village regulations that are formed do not conflict with higher statutory regulations and the public interest. With such a problem formulation, the research was carried out focusing on the village development bureau and sample villages randomly taken by researchers, especially in the Minahasa district area. The research results show the design of village authority arrangements as a solution to the two forms of villages in the law. However, compliance with the principle of recognition also needs to be emphasized, where the higher government must recognize whatever authority the village has.